A reanalysis of the structure of Tagalog verbs - De Guzman, Videa P. (Philippine Journal of Linguistics, 1980)
This paper purports to present what I think is an unorthodox and, perhaps, a revolutionary way of viewing the structure of Tagalog verbs. First, I will show that in the traditional analysis, the distinction between inflectional affixes and derivational affixes is obscure; that the analysis always results in an unwieldy list of complex affixes that defies any unified account of lexical relations. Second, I will demonstrate an analysis which distinguishes a constant set of voice inflectional affixes that are attached to various kinds of non-derived and derived verb stems. Finally, I will point out certain advantages and implications of the proposed analysis.